PERANCANGAN BLUE PRINT JARINGAN MENGGUNAKAN VIRTUAL LAN (VLAN) DENGAN STUDI KASUS (PT. PLN PERSERO AREA KUDUS) - Puspito, Faesol; Widyastuti, Naniek; Triyono, Joko (Jurnal Jarkom, 2014)
ABSTRACTThe development of computer network technology is growing rapidly as the current needs of people who use computer networks. It is seen from the number of companies or organizations that use computer networks. Thus the increasing needs and the increasing number of network users, the network also required the presence of forms that provide maximum results, both in terms of the efficiency of the network device, configuration and security. Based on these conditions, conducted an analysis of the existing network, which includes the structure, network topology, network devices. From the analysis it made the design blueprint of the new network by using VLAN. Prior to implementation, the first blueprint for a VLAN network is simulated using Packet Tracert. There are several advantages of a VLAN network, among others, can manage the switch manageable. In terms of flexibility, users on the same VLAN network is not dependent on the physical layout or location of the user is located. Moreover, in terms of availability. The use of VLANs also provide a higher level of security, since each user can not just go into the switch and dependent with other users.Keywords : VLAN, blue print, switch.